Effects of operating conditions on evaporation rate and wall shear stress development in a micro-gap heat sink with internal micro-fins - Ahmed, Shugata; Sulaeman, Erwin; Ismail, Ahmad Faris; Hasan, Muhammad Hasibul; Hanouf, Zahir (Semarak Ilmu Publishing, 2022)
Evaporation in the micro-gap heat sink has a very high heat transfer coefficient. As a result, it is significant for high heat flux management. Heat transfer rate can be enhanced further by including internal micro-fins. However, the pressure drop penalty due to the small gap height and fin surfaces is a major concern. Wall shear stress development is responsible for pressure drop. This paper investigates the effects of operating conditions, e.g., wall heat flux, pumping power, and inlet void fraction, on evaporation rate and wall shear stress development in a micro-gap heat sink with internal micro-fins of rectangular and triangular profiles, while the cross-sectional area (21.8 mm2) is kept constant. R-134a is considered as coolant. Results show that the evaporation rate from per unit volume increases with the increment of wall heat flux and decreases with the enhancement of pumping power. However, after a threshold value of the pumping power (2×10-4 W), the decrement rate falls. Again, the wall shear stress rises with the increasing wall heat flux and pumping power while reduces for escalating inlet void fraction.